2023
DOI: 10.3390/w15020352
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Reciprocity Law for UV-LEDs in Water Disinfection of Escherichia coli, Enterococcus faecalis, and Clostridium perfringens

Abstract: The aim of this study is to verify the reciprocity law in the wastewater disinfection process using UV light. The optical power UV-LEDs used were 1.6 mW and 50 mW, and the wavelengths were 265 nm and 275 nm. E. coli, Enterococcus faecalis, and Clostridium perfringens were the three microorganisms analysed in the study. The results showed lower inactivation rates around 0.063–0.065 cm2/mJ for 265 nm and 0.047–0.049 cm2/mJ for 275 nm for the Clostridium perfringens compared with the other two bacteria. For E. co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…In addition, in the three studies, E. coli was shown to be the test organism most sensitive to UV, followed by E. faecalis; and C. perfringens was the most resistant. These facts were also corroborated by Kamel et al [15] for all three bacteria in real wastewater samples, during a similar experimentation for the reciprocity law with UV LEDs. On the other hand, the slow inactivation of C. perfringens (vegetative + including spores) indicated the low susceptibility of this strain to solar disinfection, mainly due to its high resistance as a bacterial spore-forming species.…”
Section: (Table A1 In Appendix A)supporting
confidence: 81%
See 3 more Smart Citations
“…In addition, in the three studies, E. coli was shown to be the test organism most sensitive to UV, followed by E. faecalis; and C. perfringens was the most resistant. These facts were also corroborated by Kamel et al [15] for all three bacteria in real wastewater samples, during a similar experimentation for the reciprocity law with UV LEDs. On the other hand, the slow inactivation of C. perfringens (vegetative + including spores) indicated the low susceptibility of this strain to solar disinfection, mainly due to its high resistance as a bacterial spore-forming species.…”
Section: (Table A1 In Appendix A)supporting
confidence: 81%
“…They observed that at the shortest wavelength (265 nm), the inactivation rate of E. coli depended solely on the UV dose, whereas at longer wavelengths (275, 285 and 295 nm), the inactivation rate did not follow the law of reciprocity, as it depended on both irradiance and exposure time. On the other hand, Kamel et al [15] argued that this law was valid when they tested the disinfection of E. coli, E. faecalis, and C. perfringens in natural wastewater samples, using 265 nm LEDs with optical powers of 2.5 mW and 50 mW, and 275 nm LEDs with powers of 1.6 mW and 50 mW.…”
Section: Reciprocity Law In Microbial Water Disinfectionmentioning
confidence: 99%
See 2 more Smart Citations
“…This process is generally straightforward and does not require the addition of chemicals. However, managing UV lamps, monitoring UV intensity, and integrating with other methods can introduce some complexity [1][2][3][4]21].…”
Section: Introductionmentioning
confidence: 99%